A recessively inherited windmill-vane camptodactyly/ichthyosis syndrome. Issue 2 (April 1983) - Baraitser, M; Burn, J; Fixsen, J
Abstract : A brother and sister are described with a syndrome, not previously reported, of distal arthrogryposis, facial immobility, and generalised ichthyosis.